Étude et restauration de deux sculptures de jardin en terre cuite - Sabrina Vétillard (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The study and the restoration of two sphynges in terra-cotta, particularly degraded by their outdoor installation, allowed to deepen the knowledge of stamping techniques, to characterize the properties of terra-cottas and mechanisms of degradation bound to the frost. The different techniques used were the opportunity to think about limits of intervention for garden installed sculptures.